The Relative Importance of the Small Intestine and the Liver in Phase II Metabolic Transformations and Elimination of p-Nitrophenol Administered in Different Doses in the Rat - Attila Almási; Pál Perjési; Emil Fischer (MDPI AG, 2020)
Intestinal and hepatic function have been investigated in phase II metabolic reactions and elimination of p-nitrophenol (PNP) in the rat. A jejunal loop was cannulated and recirculated with isotonic solutions containing PNP in different concentrations (0, 20, 100, 500, 1000 µM). Samples were obtained from the perfusate at given intervals. To investigate the metabolic and excretory functions of the liver, the bile duct was cannulated, and the bile was collected. Metabolites of PNP were determined by validated HPLC (high pressure liquid chromatography) methods. The results demonstrated the relative importance of the small intestine and the liver in phase II metabolic transformations and elimination of PNP. There were significant differences between the luminal and biliary appearances of p-nitrophenol-glucuronide (PNP-G) and p-nitrophenol-sulfate (PNP-S). The PNP-G appeared in the intestinal lumen at the lower PNP concentrations (20 µM and 100 µM) at higher rate than in the bile. No significant difference was found between the intestinal and the biliary excretion of PNP-G when PNP was administered at a concentration of 500 µM. However, a reverse ratio of these parameters was observed at the administration of 1000 µM PNP. The results indicated that both the small intestine and the liver might play an important role in phase II metabolic reactions and elimination of PNP. However, the relative importance of the small intestine and the liver can be dependent on the dose of drugs.